2018
DOI: 10.31024/ajpp.2018.4.5.3
|View full text |Cite
|
Sign up to set email alerts
|

Historical aspects, Medicinal uses, Phytochemistry and Pharmacological review of Bauhinia variegata

Abstract: For humans, the most important necessities are food, clothes, shelter and good health. For good health, nature is full of remedies which help in curing various pathological disorders. From ancient time, herbs are being constantly used for the cure of various disorders as it has been observed that natural therapy is most efficacious than the synthetic one. Bauhinia variegata is a small to medium-sized tree. It grows to a height of about 10-12 m and is deciduous. It is mostly grown in tropical region. The genus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…BV is used for ornamental purposes [ 15 ] and as fuel with a calorific value ranging from 20.08 to 20.54 MJ/kg [ [16] , [17] , [18] ]. The chemical compounds of the seed oil obtained after extraction contain oleic acid, linoleic acid, palmitic acid, and stearic acid [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…BV is used for ornamental purposes [ 15 ] and as fuel with a calorific value ranging from 20.08 to 20.54 MJ/kg [ [16] , [17] , [18] ]. The chemical compounds of the seed oil obtained after extraction contain oleic acid, linoleic acid, palmitic acid, and stearic acid [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bauhinia belongs to the family Fabaceae and is a large genus of flowering plants that naturally occur in subtropical forest ecosystems with various forms such as trees, shrubs, and climbers [1]. Fifteen species of Bauhinia are generally grown in India [2]. Bauhinia retusa Roxb.…”
Section: Introductionmentioning
confidence: 99%
“…Nature is full of remedies that help in relieving various pathological disorders. Herbs have constantly been used from prehistoric times for the cure of various disorders as it has been observed that natural therapy is most effective than synthetic ones [1].…”
Section: Introductionmentioning
confidence: 99%